Power Quality Improvement in QUCEST Larkana Campus by Using Three Types of Power Filters - D. M. Soomro; S. C. Chong; Z. A. Memon; F. Abbasi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The increase of power electronic converters at the end-user side is unavoidable and it will cause current harmonic distortion and wide range of disturbance in the power system (PS). This paper presents current harmonic compensation for the test case of the Quaid-e-Awam University College of Engineering Sciences and Technology (QUCEST) Larkana campus in MATLAB SIMULINK by using three types of power filters i.e. passive, active and hybrid power filters. The purpose of this experiment and simulation model is to analyse and find out the best solution for reducing the current harmonic and unbalanced load condition at the incoming transformer to the campus. Moreover, this paper presents the testing and comparison of the active and hybrid power filters by using the combined design technique of harmonic compensate control system based on Unit Vector Template (UVT) and Instantaneous Reactive Power (IRP) theory. The simulation results allow to identify the effectiveness of the control system along with passive filter. Based on the testing and simulation results of three types of power filters, hybrid power filter has the maximum ability to mitigate the current harmonic in the system, and it also reduces the neutral current thus causing less stress in the existing system.